New Kings of Crude : China, India, and the Global Struggle for Oil in Sudan and South Sudan. - Patey, Luke (Hurst, 2014)
In the past decade, the need for oil in Asia's new industrial powers, China and India, has grown dramatically. The New Kings of Crude takes the reader from the dusty streets of an African capital to Asia's glistening corporate towers to provide a first look at how the world's rising economies established new international oil empires in Sudan, amid one of Africa's longest-running and deadliest civil wars. For over a decade, Sudan fuelled the international rise of Chinese and Indian national oil companies. But the political turmoil surrounding the historic division of Africa's largest country,